PENGARUH STRUKTUR KEPEMILIKAN DAN KARAKTER EKSEKUTIF TERHADAP PENGHINDARAN PAJAK DI INDONESIA Studi pada Perusahaan Manufaktur yang terdaftar di BEI periode tahun 2012-2014 - Annena Destia Hensa Saputri (AKT 16 UMY 048, 2016)
The purpose of this research is to examine the effect of institutional ownership structure, managerial ownership structure and executive character toward tax avoidance in Indonesia at manufacture companies that listed in Bursa Efek Indonesia (BEI). Population in this research is manufacture companies that listed in BEI in period of 2012 through 2014. Sample is determined with purposive sampling method, for 74 companies. This research data is obtained from Indonesian Capital Market Directory (ICMD) and www.idx.co.id. Multiple linear regression method is used as data analyze method in this research. The result shows that institutional ownership structure and managerial ownership structure have a negative and significant effect toward tax avoidance in Indonesia. Meanwhile, executive character variable has a positive and significant effect toward tax avoidance in Indonesia. Keywords : institutional ownership structure, managerial ownership structure, executive character, tax avoidance